Performance Study of a Floricultural Greenhouse Surrounded by Shallow Water Ponds - Misra, Debajit; Ghosh, Sudip (International Journal of Renewable Energy Development, 2017)
In the present paper, an innovative low energy-intensive evaporative cooling system has been proposed for greenhouse application in near-tropical regions dominated by hot climate. The system can operate under dual- ventilation mode to maintain a favourable microclimate inside the greenhouse. A single ridge type un-even span greenhouse has been considered, targeting a few species of Indian tropical flowers. The greenhouse has a continuous roof vent as well as adjustable side vents and is equipped with exhaust fans on top and roll-up curtains on the sides. The greenhouse is surrounded by shallow water ponds outside its longitudinal walls and evaporative surfaces partially cover the free water surface. Inside the pond, low cost evaporative surfaces are so placed that they form air channels.Â  Thus, outside air flows through the channels formed by the wetted surfaces over the water surface and undergoes evaporative cooling before entering the greenhouse. A simplified theoretical model has been presented in this paper to predict the inside greenhouse air temperature while ambient weather data are used as model inputs. The study reveals that during average radiation periods, the greenhouse can depends solely on natural ventilation and during peak radiation hours fan-induced ventilation is needed to maintain the required level of temperature. It is seen that under dual-ventilation mode greenhouse, temperature can be kept 3-6 oC lower than ambient temperature when saturation effectiveness is 0.7 and with 75% shading.Article History: Received February 25th 2017; Received in revised form April 14th 2017; Accepted May 4th 2017; Available onlineHow to Cite This Article: Misra, D. and Ghosh, S. (2017) Performance Study of a Floricultural Greenhouse Surrounded by Shallow Water Ponds. International Journal of Renewable Energy Development, 6(2), 137-144.https://doi.org/10.14710/ijred.6.2.137-144